Penguatan Ketahanan Pangan Berbasis Sekolah melalui Edukasi Pupuk Organik Cair dan Analisis Kesadaran Lingkungan Siswa Berdasarkan NEP dan SDGs: Strengthening School-Based Food Security through Liquid Organic Fertilizer Education and the Analysis of Students' Environmental Awareness Based on the NEP and SDGs - Nazwa Aida Dwi Agustina; Muhammad Fajar Sidik; Arini Dias Wulandari; Nasha Nurfadilah; Bilqis Zalva Denero; Farelina Dinda Benaya Nursin; Nezla Haelila Ainurohmah; Aulia Azizah Rahmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Food security is an integral component of sustainable development efforts and can be strengthened by leveraging vocational schools as spaces for learning and agricultural practice. This activity was conducted at SMK Negeri 15 Pandeglang, using the school garden as an educational medium to process organic waste into liquid organic fertilizer, accompanied by an assessment of students’ environmental awareness and understanding of food security. Data were collected through field observations, activity documentation, and questionnaires administered before and after the implementation. The use of the school garden demonstrated its potential as a contextual learning platform, although several limitations were identified, including constraints in facility management, pest disturbances, and limited utilization of harvest products. The educational and practical activities fostered a deeper understanding of natural resource limitations, ecosystem balance, and the importance of diversification and effective use of agricultural outputs. Overall, the activity helped strengthen students’ environmental awareness, motivation, and readiness to apply sustainable agricultural practices to support school-based food security.